2016
DOI: 10.4103/2279-042x.192461
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of five common drug–drug interaction software programs regarding accuracy and comprehensiveness

Abstract: Objective:Drug–drug interactions (DDIs) can cause failure in treatment and adverse events. DDIs screening software is an important tool to aid clinicians in the detection and management of DDIs. However, clinicians should be aware of the advantages and limitations of these programs. We compared the ability of five common DDI programs to detect clinically important DDIs.Methods:Lexi-Interact, Micromedex Drug Interactions, iFacts, Medscape, and Epocrates were evaluated. The programs' sensitivity, specificity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(37 citation statements)
references
References 22 publications
0
35
0
2
Order By: Relevance
“…In fact, it is a known problem that different DDI screening tools offer different sensitivity and specificity. Furthermore, it has also been reported that DDI databases under-report clinically relevant DDIs and in some cases, over report insignificant drug interactions [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is a known problem that different DDI screening tools offer different sensitivity and specificity. Furthermore, it has also been reported that DDI databases under-report clinically relevant DDIs and in some cases, over report insignificant drug interactions [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Educational outreach is one possible solution, although the fact that 79.1% of the participants in this study had recently undergone CME in pain management dampens enthusiasm. Software tools have been shown to help [ 22 ] as have team-based approaches involving pharmacists [ 23 ]. More of these solutions could be implemented.…”
Section: Discussionmentioning
confidence: 99%
“… An interaction check was undertaken between clozapine and all medicines, using Lexicomp ® [ 13 ] and Stockley’s Interaction Checker (SIC) [ 14 ]. Lexicomp ® is a widely accessible drug interaction software program and studies show it provides the most competent, complete, and user-friendly applications [ 15 ]. SIC is a comprehensive and authoritative international reference book on DDIs.…”
Section: Methodsmentioning
confidence: 99%